Challenges of employment in the agrifood sector of developing countries—a systematic literature review - Tamás Mizik; Judit Nagy; Endre Mihály Molnár; Zalán Márk Maró (Humanities & Social Sciences Communications)
Abstract Agri-food employment in developing countries holds significant importance due to the vital role of the sector. This study synthesizes existing literature to identify the key challenges of employment in the agri-food sector in developing countries. 17,125 articles were identified in the Scopus database and based on a two-stage systematic review of 173 articles (final database), six principal topics were identified and analyzed: (1) family farms; (2) special characteristics of employment; (3) gender disparities; (4) wages; (5) education; (6) productivity. Each segment provided important results. Family farms were found to be crucial for employment, production, and income generation in developing countries. The special characteristics of employment often involve migration and mobility challenges, while gender inequalities persist due to the special nature of production. Agricultural wages are lower compared to other sectors, further accelerating outmigration. Education plays a key role to adopting advanced production methods, but educated people often find better opportunities outside the sector. Finally, productivity is crucial in income generation and is often driven by mechanization. These six segments are interconnected, with education emerging as a key factor. This study contributes to the existing literature by providing a systematic and comprehensive synthesis of the employment challenges in the agri-food sector of developing countries and providing targeted insights for policymakers to address pressing issues such as gender inequality or low agricultural productivity.